The Ferrier Lecture 2004 what can transcranial magnetic stimulation tell us about how the brain works? - Cowey, A (2005)
Transcranial magnetic stimulation (TMS) is a technique whereby parts of the cerebral cortex and underlying white matter can be excited by a brief electrical current induced by a similarly brief, rapidly fluctuating magnetic field which is itself produced by rapidly discharging a current through an insulated coil held against the scalp. When combined with magnetic resonance structural and functional images of the subject's brain, the stimulation can be directed at specific cortical areas. Over a period of only 15 years, TMS has revealed hitherto unsuspected aspects of brain function, such as the role of distant parts of the brain in recovery from stroke, and has helped to resolve several previously intractable disputes, such as the neuronal basis of conscious awareness. This article describes and discusses the origins and nature of TMS, its applications and limitations, and its especial usefulness in conjunction with other techniques of evaluating or imaging brain activity.